Learning Obstacle Of Prospective Mathematics Teachers On Real Analysis - Badjeber, Rafiq; Sukayasa, I Wayan; Hadi, Windia; Melissa, Margareta Madha (Program Studi Tadris Matematika dan Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Universitas Islam Negeri (UIN) Datokarama Palu, 2025)
This study aims to identify the learning obstacles experienced by prospective mathematics teachers when constructing proofs in real analysis. This study uses a qualitative method with a case study design. The research subjects comprised 20 third-year prospective mathematics teachers at a university in Palu. Five prospective mathematics teachers were selected for interviews based on the types of obstacles they experienced. The research instruments included a respondent ability test (RAT) and interview guidelines. Data analysis was conducted by reducing data, presenting data, and drawing conclusions. The results of the study indicate that prospective mathematics teachers experience ontogenic obstacles, namely difficulty in thinking deductively and axiomatically; epistemological obstacles when difficulty in understanding definitions, difficulty in starting proofs, and difficulty in constructing complete proofs; and didactical obstacles that occur due to a procedural learning approach. These findings can be used by lecturers in designing relevant learning designs based on prospective mathematics teachers' learning trajectories to anticipate potential learning obstacle